Improvement of a Three-Layered in vitro Skin Model for Topical Application of Irritating Substances - Schmidt, Freia F.; Nowakowski, Sophia; Kluger, Petra J. (Frontiers in Bioengineering and Biotechnology, 2020)
In the field of skin tissue engineering, the development of physiologically relevant in vitro skin models comprising all skin layers, namely epidermis, dermis and subcutis, is a great challenge. Increasing regulatory requirements and the ban on animal experiments for substance testing demand the development of reliable and in vivo-like test systems, which enable high-throughput screening of substances. However, the reproducibility and applicability of in vitro testing has so far been insufficient due to fibroblast-mediated contraction. To overcome this pitfall, an advanced 3-layered skin model was developed. While the epidermis of standard skin models showed an 80% contraction, the initial epidermal area of our advanced skin models was maintained. The improved barrier function of the advanced models was quantified by an indirect barrier function test and a permeability assay. Histochemical and immunofluorescence staining of the advanced model showed well-defined epidermal layers, a dermal part with distributed human dermal fibroblasts and a subcutis with round-shaped adipocytes. The successful response of these advanced 3-layered models for skin irritation testing demonstrated the suitability as an in vitro model for these clinical tests: only the advanced model classified irritative and non-irritative substances correctly. These results indicate that the advanced set up of the 3-layered in vitro skin model maintains skin barrier function and therefore makes them more suitable for irritation testing.